Calreticulin regulates Src kinase in osteogenic differentiation from embryonic stem cells - Zahra, Alvandi (2020)
Calreticulin, the major Ca2+ buffer of the endoplasmic reticulum plays an important role in the choice of fate by embryonic stem cells. Using the embryoid body method of organogenesis, we showed impaired osteogenesis in crt−/− cells vis-à-vis calreticulin-containing osteogenic WT cells. In the non-osteogenic crt−/− cells, c-Src- a non-receptor tyrosine kinase- was activated and its inhibition rescued osteogenesis. Most importantly, we demonstrated that calreticulin-containing cells had lower c-Src kinase activity, and this was accomplished via the Ca2+-homeostatic function of calreticulin. Specifically, lowering cytosolic [Ca2+] in calreticulin-containing osteogenic WT cells with BAPTA-AM, activated c-Src and impaired osteogenic differentiation. Conversely, increasing cytosolic [Ca2+] in crt−/− cells with ionomycin deactivated c-Src kinase and restored osteogenesis. The immediate effector of calreticulin, the Ser/Thr phosphatase calcineurin, was less active in crt−/− cells, however, its activity was rescued upon inhibition of c-Src activity by small molecule inhibitors. Finally, we showed that higher activity of calcineurin correlated with increased level of nuclear Runx2, a transcription factor that is the master regulator of osteogenesis. Collectively, our work has identified a novel pathway involving calreticulin regulated Ca2+ signalling via c-Src in osteogenic differentiation of embryonic stem cells.